Workplace sustainability: energy-saving behaviors in office environments of Thailand - Hnin, Su Wutyi; Javed, Amna; Karnjana, Jessada; Jeenanunta, Chawalit; Kohda, Youji (Frontiers in Psychology, 2025)
IntroductionEnergy consumption in office environments significantly impacts global energy usage, particularly due to lighting, air conditioning, and electronic devices. Urbanization and economic growth in Thailand exacerbate energy demands, positioning office environments as essential for energy conservation efforts. Traditional strategies have primarily focused on technological solutions, but these approaches often fail to address the pivotal role of human behavior in shaping energy consumption.MethodsThis study develops a culturally contextualized framework by integrating the Motivation-Opportunity-Ability (MOA) model, the Norm Activation Model (NAM), and the Theory of Planned Behavior (TPB) to examine key determinants of workplace energy-saving behavior. Data were collected from 105 office workers in Bangkok, Thailand, through an online survey. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), this study validated the framework to analyze the relationships between motivation, opportunity, ability, intention, and behavior within hierarchical workplace structures and collective decision-making settings.ResultsThe results highlight motivation and ability as significant predictors of energy-saving behavior, reinforcing the role of awareness of consequences, personal norms, and perceived control. However, opportunity, intention, and individual comfort exhibit negative relationships with energy-saving behavior, suggesting that structural policies, behavioral intentions, and thermal satisfaction interact in complex ways.ConclusionThese findings underscore the importance of contextually adaptive workplace policies that account for behavioral and structural energy conservation challenges. By providing a culturally sensitive framework, this study offers insights for policymakers and organizational leaders to develop effective and sustainable energy-saving strategies that integrate behavioral considerations alongside technological interventions.